Climate-smart aquaculture: Evidences and potentials for northern coastal area of Vietnam - Tu Trinh; Nhuong Tran; Quyen Cao (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
Coastal aquaculture, particularly brackish water shrimp farming, plays an important role in the socio-economic development of most coastal communities on the North Central Coast (NCC) of Vietnam. However, coastal aquaculture in the region is among the activities most affected by increasing global climate change, which threatens sustainable development of the fisheries sector, as well as food security of the country. Within the action plan framework for adaptation and mitigation for climate change in the Ministry of Agriculture and Rural Development and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), climate-smart aquaculture (CSA) trials have been conducted in Hoang Phong commune, Thanh Hoa province in 2015 by WorldFish, the Vietnam Institute of Economics and Planning (VIFEP) and Thanh Hoa Agriculture Extension Center (TEC). In the farm-level climate-smart aquaculture trials, tilapia was raised in rotation with tiger shrimp, mud-crab and seaweed in a traditional extensive aquaculture system. Initial results show that the aqua-smart practice under the CSA approach is a “triple win” for local aquaculture farmers through: (1) sustainably improving aquaculture productivity and farming efficiency of the current production system; (2) increasing adaptive capacity and resilience of coastal aquaculture to climate change; and (3) contributing to climate change mitigation. However, a number of constraints, such as lack of high-quality fish seed and feeds, low market uptake for tilapia and uncertainty from extreme climate events, should be considered in scaling out the aqua-smart practice throughout the region.